The Radical Scavenging Activities and Anti-Wrinkle Effects of Soymilk Fractions Fermented with Lacticaseibacillus paracasei MK1 and Their Derived Peptides - Sulhee Lee; Sang-Pil Choi; Huijin Jeong; Won Kyu Yu; Sang Won Kim; Young-Seo Park (MDPI AG, 2023)
Soybean-derived peptides exert several beneficial effects in various experimental models. However, only a few studies have focused on the radical scavenging and anti-wrinkle effects of soymilk-derived peptides produced via different processes, such as fermentation, enzymatic treatment, and ultrafiltration. Therefore, in this study, we investigated the radical scavenging and antiwrinkle effects of soymilk fractions produced using these processes. We found that 50SFMKUF5, a 5 kDa ultrafiltration fraction fermented with Lacticaseibacillus paracasei MK1 after flavourzyme treatment, exhibited the highest radical scavenging activity using the 2,2-diphenyl-1-picrylhydrazyl radical scavenging assay as well as potent anti-wrinkle effects assessed by type 1 procollagen production and tumor necrosis factor-α production in ultraviolet B (UVB)-treated human dermal fibroblasts and HaCaT keratinocytes. To identify potential bioactive peptides, candidate peptides were synthesized, and their anti-wrinkle effects were assessed. APEFLKEAFGVN (APE), palmitoyl-APE, and QIVTVEGGLSVISPK peptides were synthesized and used to treat UVB-irradiated fibroblasts, HaCaT keratinocytes, and α-melanocyte-stimulating hormone-induced B16F1 melanoma cells. Among these peptides, Pal-APE exerted the strongest effect. Our results highlight the potential of soymilk peptides as anti-aging substances.